A new species of Pseudopaludicola Miranda-Ribeiro (Leiuperinae: Leptodactylidae: Anura) from the Cerrado of southeastern Brazil - de Andrade, Felipe Silva; de Carvalho, Thiago Ribeiro (Zootaxa, 2013)
A new species of Pseudopaludicola is described from the Cerrado of southeastern Brazil. Pseudopaludicola facureae sp. nov. is diagnosed from the P. pusilla species group by the absence of either T-shaped terminal phalanges or toe tips expanded, and distinguished from almost all recognized taxa currently assigned to Pseudopaludicola (except P. canga, P. giarettai, and P. hyleaustralis) by possessing a non-pulsed advertisement call. However, the advertisement call of the new species consists of the emission of well-defined call series, whereas the advertisement call of P. giarettai is long (117–187 ms) and with an isolated emission pattern; respecting to P. canga, the new species emits very long notes series (up to 53 notes/advertisement call), compared to the short call series of P. canga (up to 9 notes/advertisement call); considering P. hyleaustralis, the new species has a shorter note duration (15–35 ms), higher note rate per minute (480–1860), and higher dominant frequency (4076–5108).